Pengaruh Karakteristik Organisasi Terhadap Pemanfaatan Posbindu Penyakit Tidak Menular Di Wilayah Puskesmas Helvetia - Riri Astika Indriani; Zulfendri Zulfendri; Surya Utama (Berita Kedokteran Masyarakat (BKM), 2018)
Effect of organization characteristics to the utilization of posbindu non communicable disease in Helvetia Public Health Center Purpose: The purpose of this research is to explain the influence of organizational characteristic (behavior of health officer, cadre behavior, service facility, Posbindu PTM activity) to the utilization of POSBINDU PTM in Helvetia Public Health Center.Methods: The type of research is survey research with explanatory research type. Sample amounted to 100 people taken with Proportionate Stratified Random Sampling technique. Primary data was obtained through direct interview using questionnaire. Data were analyzed by multiple linear regression test at the level of real test α = 5%.Results: The results showed that health officer behavior, cadre behavior, service facility influence PT Posbindu utilization, while PTM Posbindu activity utilization Posbindu PTM. It is estimated that the behavior of health workers has the greatest contribution (0.636) to the utilization of POSBINDU PTM. Ability of health officer behavior variable, cadre behavior and service facility to explain the utilization of POSBINDU PTM by 91%. In general, the utilization of POSBINDU PTM will increase if health officer behavior, cadre behavior and service facility are improved.Conclusions: Suggested in increasing prevention effort and overcoming PTM to form Posbindu PTM in every village in Helvetia health center area, health officer expected to be more friendly, alert, attention in serving community in Posbindu PTM, giving training to cadre Posbindu PTM, equip facilities and infrastructure to support implementation Posbindu PTM and implement a five-table system for Posbindu PTM activities can run more regularly and efficiently.